Analisis Integrasi Teknologi dalam Pembelajaran Proyek Kolaboratif berbasis Literasi Sains - Huda, Choirul; Agustini, Ferina; Reffiane, Fine; Mudzanatun, Mudzanatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The focus of this research is to analyze Technology Integration in Collaborative Learning Projects based on Scientific Literacy for students of the PGSD Study Program at PGRI University Semarang. The ability to integrate and collaborate on learning is necessary to produce useful project products.The research method used is a qualitative descriptive method. The research subjects were students of the PGSD study program at PGRI University Semarang. Research success can be seen from 4 indicator aspects: (1) Combining various skills possessed by each student in the good category (56.1%), (2) increasing the efficiency and productivity of work produced in the good category (44.9%), (3) Reducing the risk of failure of products produced in the good category (44.9%), and (4) Increasing creativity and innovation in the good category (40.9%).